2015
DOI: 10.1007/s00167-015-3533-8
|View full text |Cite
|
Sign up to set email alerts
|

Sagittal patellar tilt and concomitant quadriceps hypotrophy after tibial nailing

Abstract: This study revealed that patellofemoral joint kinematics in the operated extremity was diminished in the sagittal plane correlating with the quadriceps muscle volume loss and gracilis muscle hypertrophy. The modalities focused on both preventing and treating the hypotrophy of the quadriceps muscle following the surgical treatment of tibial fracture, which may help to overcome this quite common pathology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(37 citation statements)
references
References 29 publications
2
23
1
Order By: Relevance
“…To the best of our knowledge, it was the first study analysing the patellofemoral joint alignment from the sagittal plane point of view in patients with anterior knee pain. The main difference between the findings of this study [2] and the previous study is that, although the P-PT angle was increased in the knees of patients suffering from anterior knee pain following tibial nailing with respect to their normal side, it was found to be lower in patients with chondromalacia patella with respect to the control group. Patellar flexion in the sagittal plane is a natural component of patellofemoral tracking in the sagittal plane [33,39].…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…To the best of our knowledge, it was the first study analysing the patellofemoral joint alignment from the sagittal plane point of view in patients with anterior knee pain. The main difference between the findings of this study [2] and the previous study is that, although the P-PT angle was increased in the knees of patients suffering from anterior knee pain following tibial nailing with respect to their normal side, it was found to be lower in patients with chondromalacia patella with respect to the control group. Patellar flexion in the sagittal plane is a natural component of patellofemoral tracking in the sagittal plane [33,39].…”
Section: Discussioncontrasting
confidence: 99%
“…In our previous report, the P-PT angle was used to analyse sagittal plane patellofemoral alignment. In these reports [2], it was revealed that the changes in the P-PT angle were correlated…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Song et al found that the knee ROM was significantly associated with the severity of knee pain [22]. Moreover, Aksahin et al [26] found that the damage to quadriceps might worsen the patellar tilt due to the sagittal patellar tilt and quadriceps hypotrophy after tibial nailing, besides, the displacement of patella might have a negative impact on the knee function. Therefore, much attention must be paid to minimize the damage to quadriceps, especially in SP IMN insertion.…”
Section: Discussionmentioning
confidence: 99%
“…However, the sensitivity, specificity, and AUC of the cutoff value is relatively lower (sensitivity: 70.3%, specificity: 57.6%, AUC: 0.696) to be used generally. Furthermore, to the best of our knowledge, there was no previous study to determine the PPTA cutoff value in the disease groups and some previous studies reported the normal mean PPTA value as 145.1° [ 3 , 20 ]. Further studies are needed to determine the normal value and statistically significant cutoff value of PPTA.…”
Section: Discussionmentioning
confidence: 99%